Association between prepartum metabolic status and resumption of postpartum ovulation in dairy cows - Miqueo, E. (2019)
Cows transitioning from late gestation to early lactation experience an increase in energy demands, which lead to a negative energy balance (NEB) because the greater energy requirement is not fully synchronized with the intake of dry matter. In this context, there is an increase in plasma NEFA and ghrelin concentrations and a decrease in plasma insulin and glucose-dependent insulinotropic polypeptide (GIP) concentrations. This situation could have a negative impact on the return to cyclicity because some of these variables have been associated with reduced GnRH and LH pulsatility (high NEFA and low insulin concentrations). However, there are no studies showing the relationship between ghrelin or GIP and reproductive performance. It is known that these hormones are related with lipolysis and NEB, with NEB being one of the main determinants of GnRH pulse generator activity. Thus, the objective of the present study was to evaluate the association between plasma NEFA concentration and metabolic hormones (insulin, ghrelin, and GIP) before parturition and their associations with the resumption of postpartum ovulations in dairy cows. A completely randomized block design was used in a commercial dairy herd with sampling day (visit to farm) as the blocking criteria. Holstein cows (n = 92) were screened for plasma NEFA concentration -5 d (+/-2 d) relative to the expected parturition day, and top and bottom quartiles were considered as high (H-NEFA) and low (L-NEFA) NEFA groups. Data were analyzed with correlation, linear regression, and proportional hazard regression models. Plasma NEFA concentration (H-NEFA mean ¼ 294 mM, SD ¼ 141.2; and L-NEFA mean ¼ 122 mM, SD ¼ 25.3) was correlated (P < 0.01) with plasma insulin (r2 = 0.374) and ghrelin (r2 = 0.346) concentrations but not with plasma GIP concentration (P = 0.64). The greater the concentration of insulin, the lesser the prepartum NEFA concentration (for each 1 mU/mL of plasma insulin increase, there is a decrease of 1.223 +/- 0.62 mM of NEFA). Plasma ghrelin and GIP concentrations were not associated with plasma NEFA concentration. Finally, H-NEFA prepartum cows were less likely to resume ovulation than L-NEFA cows (hazard ratio [HR] = 0.563, 95% confidence interval [CI] = 0.314–1.011), whereas high ghrelin cows were more likely to resume ovulation than low ghrelin cows (HR = 1.873, 95% CI = 0.846–4.145). Conversely, resumption of ovulation was not associated with prepartum insulin and GIP concentrations. Prepartum NEFA and possibly ghrelin are associated with the return to postpartum cyclicity; however, insulin and GIP are not related to the resumption of ovulation in dairy cows.